Regulating Intimacy : A New Legal Paradigm - Cohen, Jean L., 1946- (Book collections on Project MUSE., 2002)
The regulation of intimate relationships has been a key battleground in the culture wars of the past three decades. In this bold and innovative book, Jean Cohen presents a new approach to regulating intimacy that promises to defuse the tensions that have long sparked conflict among legislators, jurists, activists, and scholars. Disputes have typically arisen over questions that apparently set the demands of personal autonomy, justice, and responsibility against each other. Can law stay out of the bedroom without shielding oppression and abuse? Can we protect the pursuit of personal happiness wh.